Research on solar cell preparation technology for cutting-edge technology - Ji, Zhuoran (Transactions on Engineering and Technology Research, 2024)
Flexible dye-sensitized solar cells are highly valued as a practical technology with low production costs. In this paper, we study flexible dye-sensitized solar cells consisting of nanocrystalline TiO2 thin-film electrodes based on titanium metal and counter electrodes based on conductive coated polymers. In order to improve the photoelectric conversion efficiency, nanocrystalline TiO2 film electrodes and TiO2 nanotube film electrodes based on titanium metal and TiO2 nanotube film electrodes are prepared by DC low-field electrophoretic deposition, electrochemical anodizing and screen printing under DC and pulse voltages combined with high-temperature sintering methods; and platinum-carrying counter electrodes and carbon counter electrodes based on conductive coated polymers are prepared by low-temperature techniques, such as constant-current electrochemical deposition and chemical reduction. The mechanisms and characteristics of different preparation methods and optimization techniques are analyzed and discussed, and the performances of nanocrystalline TiO2 thin film electrodes and counter electrodes prepared by different methods are compared. On this basis, the all-flexible solar cell is developed, and the maximum photoelectric conversion efficiency reaches 6.74%.